Adolescence and Hormones: Array - Furtună, Alexandra Gabriela (New Trends in Psychology, 2020)
The adolescent period is a delicate period of transition, when a child steps into the world of maturity. Naturally, the physical, emotional and mental changes of the young person at the maturity threshold occur. Such changes are caused by hormonal processes that help a child to evolve, reach maturity. Today’s teens are exposed to hundreds of chemicals, compared to teens from previous generations. The chemicals are present in the form of pesticides in fruits and vegetables, plastics, products for maintaining beauty, etc. and once they enter the body it causes a lot of hormonal problems.